The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1042/bst20130203
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for the treatment of ovarian cancer

Abstract: Ovarian cancer usually responds well to chemotherapy, but once the disease becomes resistant to chemotherapy, the treatment options available are inadequate. A number of strategies are currently undergoing clinical evaluation, among which angiogenesis and PARP [poly(ADP-ribose) polymerase] inhibitors appear promising. Pre-clinical studies have identified several potential new therapeutic strategies, and we review the potential for use of BH3 (Bcl-2 homology) mimetics, autotaxin inhibitors and statins to treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…However, many patients experience recurrence and chemotherapy resistance, even though they response well initially. Consequently, the overall 5-year survival rate is about 40% after diagnosis with advanced-stage ovarian cancer [3]. Thus, effective and accessible adjuvant interventions for advanced-stage ovarian cancer are required.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, many patients experience recurrence and chemotherapy resistance, even though they response well initially. Consequently, the overall 5-year survival rate is about 40% after diagnosis with advanced-stage ovarian cancer [3]. Thus, effective and accessible adjuvant interventions for advanced-stage ovarian cancer are required.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, emerging evidences supported the involvement of elevated cholesterol in reprogramming of metabolic program which augments the process of tumor development [6]. It has been suggested that statins inhibit cancer development through their inhibition of the mevalonate pathway, which could modify several proteins which is particularly necessary for the function of cancer cells, such as GTPases Ras, Rho, and Rab [3]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activity of ABT-737 has previously been attributed to inhibition of the pro-apoptotic mediators, Bcl-2, Bcl-x L or Bcl-w, of which Bcl-x L is overexpressed in ovarian cancer (8,25). Statins have been shown to induce apoptosis through a number of pathways, including suppression of Akt/Erk activation (11,12), increased phosphorylation of the p38 MAPK pathway (12), and attenuation of Mcl-1, probably through the inhibition of NF-κB (26).…”
Section: Discussionmentioning
confidence: 99%